Macromol. Chem. Phys. 9/2014. Issue 9 (May 2014) - Roth, Peter J.
<x xml:space="preserve">Abstract</x> Frontispiece: Guidance on how to compose well‐defined smart polymers with tailored properties is discussed, with a focus on responsiveness to different types of stimuli and upper and lower critical solution temperatures. A range of postpolymerization modification reactions are highlighted. Further details can be found in the article by P. J. Roth on page 825. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>